Modular Programming Still a Challenge. - Just, Louis C.; Leaf, Gary K.; Toppel, Bert J. (Communications of the ACM, 2009)
A letter to the editor is presented in response to the article "Liskov on Liskov," by Leah Hoffmann in the July 2009 issue.